Integration of Homeopathy and Complementary Medicine in the Tuscan Public Health System and the Experience of the Homeopathic Clinic of the Lucca Hospital - Rossi, E.; Di Stefano, M.; Picchi, M.; Panozzo, M. A.; Noberasco, C.; Nurra, L.; Baccetti, S. (Homeopathy, 2018)
Introduction The healthcare programs of the Region of Tuscany (Italy) have started the process of integration of some types of complementary medicine (CM), including homeopathy, which began in 1996. The Homeopathic Clinic of Lucca was opened in 1998, followed by the Homeopathic Clinic for Women in 2003, and the Clinic for CM and Diet in Oncology in 2013.Methods Observational longitudinal studies conducted on 5,877 patients (3,937 in the general clinic, 1,606 in the women's clinic and 334 in oncology) were consecutively examined from 2003 to 2016. The Outcome in Relation to Impact on Daily Living (ORIDL) was generally used to assess outcomes.Results Comparing the clinical conditions before and after homeopathic treatment, improvement was observed in 88.8% of general medicine patients with follow-up (45.1%); in particular, 68.1% of the patients had a major improvement in or resolution (ORIDL +2, +3, +4) of their condition. In women, an improvement was obtained in 74.1% cases and a major improvement in 61.2%. In cancer patients with homeopathic and integrative treatment, a significant improvement was observed for all the symptoms during anti-cancer therapy, particularly for hot flashes, nausea, depression, asthenia, and anxiety.Conclusions These results suggest that homeopathy can effectively be integrated with allopathic medicine and that the Tuscan experience could provide a useful reference for developing national and European regulations on the use of CM and homeopathy in public healthcare.
Keywords: homeopathy; complementary and integrative medicine; public healthcare; Tuscan regional experience; public homeopathic clinic